Hepatic necrosis: A main presentation of systemic lupus erythematosus in a previously healthy woman - Majid Avijgan; Mohsen Meidani; Mansour Salesi; Farshid Rezaei (International Journal of Preventive Medicine, 2011)
Systemic lupus erythematosus (SLE) is a chronic inflammatory disease of unknown cause. In this study, we report a case of SLE that was presented with persistent vomiting and liver involvement. To our knowledge, this is the first description of a patient with hepatic necrosis as the initial presentation of SLE in a previously healthy woman without any significant past medical history. In the literature, we found few cases of SLE with liver necrosis. In addition, all the cases found had a past medical history of a missed abortion or other complications of the disease. Therefore, if a young woman presents hepatic necrosis with a background of a previously missed abortion, it is better to perform anti-nuclear antibody (ANA) and anticardiolipin antibody tests as a preventive method for early diagnosis and early treatment.